2022
DOI: 10.3390/antiox11122438
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative-Stress-Associated Proteostasis Disturbances and Increased DNA Damage in the Hippocampal Granule Cells of the Ts65Dn Model of Down Syndrome

Abstract: Oxidative stress (OS) is one of the neuropathological mechanisms responsible for the deficits in cognition and neuronal function in Down syndrome (DS). The Ts65Dn (TS) mouse replicates multiple DS phenotypes including hippocampal-dependent learning and memory deficits and similar brain oxidative status. To better understand the hippocampal oxidative profile in the adult TS mouse, we analyzed cellular OS-associated alterations in hippocampal granule cells (GCs), a neuronal population that plays an important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 140 publications
1
7
0
Order By: Relevance
“…Given reports of increased DNA damage and chronic neuroinflammation in DS and the Ts65Dn brain ( Guedj et al, 2016 ; Ahmed et al, 2021 ; Puente-Bedia et al, 2022 ), we hypothesized that subpopulations of Ts65Dn cells would exhibit accelerated senescence. Senescent cells accumulate in aged tissues because of exhaustion of proliferation-competent cells ( Di Micco et al, 2021 ; Kumari and Jat, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given reports of increased DNA damage and chronic neuroinflammation in DS and the Ts65Dn brain ( Guedj et al, 2016 ; Ahmed et al, 2021 ; Puente-Bedia et al, 2022 ), we hypothesized that subpopulations of Ts65Dn cells would exhibit accelerated senescence. Senescent cells accumulate in aged tissues because of exhaustion of proliferation-competent cells ( Di Micco et al, 2021 ; Kumari and Jat, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, an intricate interplay exists between oxidative stress and proteostasis, as one of the early responses to excessive ROS is the induction of mitophagy, which can reduce oxidative damage and ROS production ( Shefa et al, 2019 ). Multiple lines of evidence have shown that ROS interacts with both ubiquitin-dependent and receptor-dependent mitophagy pathways ( De Gaetano et al, 2021 ; Puente-Bedia et al, 2022 ) ( Figure 2C ).…”
Section: Discussionmentioning
confidence: 99%
“…Given reports of increased DNA damage and chronic neuroinflammation in DS and the Ts65Dn brain [63][64][65] , we hypothesized that subpopulations of Ts65Dn cells would exhibit accelerated senescence. Senescent cells accumulate in aged tissues due to exhaustion of proliferation-competent cells 66,67 .…”
Section: Cortical Ts65dn Opcs Exhibit Enrichment For a Senescence-ass...mentioning
confidence: 99%